Does Religiosity Improve Tax Compliance? An empirical research based from gender - Dekeng Setyo Budiarto; Yennisa Yennisa; Rohmyati Widyaningrum (Jurnal Dinamika Akuntansi)
Religiosity and love of money plays an important role in determining individual compliance with tax regulations in developing countries. This research examines the influence of love of money and religiosity on tax evasion. In addition, it studies the relationship between love of money, religiosity, and tax evasion based from a gender. The research data were obtained from 8 private universities in Special Region of Yogyakarta with 207 samples and it uses convenience sampling. The number of samples was determined by convenience sampling method. Analysis data uses regression analysis. The results indicate that love of money has significant effect on tax evasion, while religiosity has no significant effect on tax evasion. There is significant difference between love of money and tax evasion from a gender perspective. The conclusion of this research is tax evasion in Indonesia determined by love of money and not given by religiosity. Moreover, sex is not an indicator in tax evasion and love of money.